PENGEMBANGAN MEDIA PUZZLE KOSAKATA DALAM PEMBELAJARAN BAHASA JERMAN SISWA KELAS XI SMA - ROHMAH, LAILATUL (LATERNE, 2016)
Vocabulary Puzzle is a new medium that can facilitate students to understand new vocabulary in German. Based on the Needs questionnaire  of students who have been deployed in Language class XI SMAN 1 Krian, showed that 80.95% of students are interested in learning media, that it is formed a game that can help students where there are 76.19% of students had difficulty in understanding new vocabulary in German. Therefore it takes the media to help students. Problem Formulation of this research is